Screen time use in children less than five years old - Ferreira, Joana; Prucha, Bárbara; Pinto, Odete; Souto, Raquel; Lima, Ricardo Peixoto; Morna, Carla (BIRTH AND GROWTH MEDICAL JOURNAL, 2020)
Introduction: While the limited use of high-quality and appropriate media may have a positive influence, excessive exposure carries health risks for young children and their families. Research suggests that increased screen time in young children is linked to negative health outcomes, including obesity, decreased cognitive and language development and reduced academic success. In this study we aimed to characterize the screen-time habits in a healthy population of children, aged between six months and five years, of two Family Healthcare Units of an urban area in northern Portugal, and to review the current literature on children’s screen time and health-related issues. Methods: This is a cross-sectional, observational and analytic study. We selected a convenience sample of children aged between six months and five years who were assessed at a scheduled surveillance visit and a questionnaire was applied to the caregivers between February and July 2018. Results: One hundred sixty-six children were included. The mean age was 30 months; 53% were males. Television dominated total screen time. About 85% of children under two years-old and 80% of infants six to 12-months-old were exposed to screens daily, with 79% of them spending up to one hour per day in front of screens. The majority of parents of children aged two years and older were present and set limits on their children’s screen use. Overall, only 39% of parents affirmed to be aware of current guidelines for screen time. In our study, children’s screen time habits were not related with parents’ socioeconomic or academic status. Parents’ knowledge about current guidelines also did not minimize children’s screen use (p=0,094). Discussion/Conclusion: Young children are exceeding screen time recommendations. Given that parents play a key role in the development of their children’s behaviors and that there is no evidence to support introducing screens at an early age, interventions to reduce children’s screen-time in the current media environment are needed.